Flexible supercapacitor electrodes based on real metal-like cellulose papers - Ko, Yongmin (Nat Commun, 2017)
The effective implantation of conductive and charge storage materials into flexible frames has been strongly demanded for the development of flexible supercapacitors. Here, we introduce metallic cellulose paper-based supercapacitor electrodes with excellent energy storage performance by minimizing the contact resistance between neighboring metal and/or metal oxide nanoparticles using an assembly approach, called ligand-mediated layer-by-layer assembly. This approach can convert the insulating paper to the highly porous metallic paper with large surface areas that can function as current collectors and nanoparticle reservoirs for supercapacitor electrodes. Moreover, we demonstrate that the alternating structure design of the metal and pseudocapacitive nanoparticles on the metallic papers can remarkably increase the areal capacitance and rate capability with a notable decrease in the internal resistance. The maximum power and energy density of the metallic paper-based supercapacitors are estimated to be 15.1 mW cm(−2) and 267.3 μWh cm(−2), respectively, substantially outperforming the performance of conventional paper or textile-type supercapacitors.